EKOWISATA MANGROVE SEBAGAI KAWASAN PERLINDUNGAN SUMBERDAYA ALAM DAN NILAI BUDAYA DI BANDAR BAKAU KOTA DUMAI - Rahmayani, Helvina; Achnes, Syofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research purposed to get known about how the mangrove ecoturism as the areas ofcultural resources and protection of cultural values in Dumai.This research used qualitative desciptive method to analyze the problems. Samples on thisresearch are 12 samples decided by cencus sampling. Whereas data collection techniques tookby observation, questionnaire, interview and documentation. And it was using likert scale toknow the length of intervals.Based on the research results, Bandar Bakau areas has already protected the naturalresources and the cultural values that Dumai city have. As for the most dominant benefit ofhaving this areas are for protection for ecological processes and conservation for biodiversityand also for preserving and protecting the local cultural values. However from seven benefit ofhaving a mangrove conservation, there are still have two benefit that still haven’t optimallyavailable in Bandar Bakau. They are financial mechanism and ecoturism mechanism, andincreasing local facilities, transportation, and communication.Key Words: Mangrove Ecoturism, Natural Resources Conservation, Cultural Values, BandarBakau Kota Dumai